HUBUNGAN ANTARA MOTIVASI BELAJAR DAN SIKAP MAHASISWA STIE AMA SALATIGA DALAM PERKULIAHAN DENGAN STRESS SEBAGAI VARIABEL KONTROL - Putra, Yanuar Surya (AMONG MAKARTI, 2010)
Abstract Attitude is one important factor for shaping human behavior, Attitude reflects the preference or non-fondness of someone on other people, objects, events and activities happening in their environment. From that understanding can be taken the notion that individual motivation will be associated with the formation of the individual's attitude to do something, not only within the scope of the working sphere but also within the scope of the learning process, especially the learning process of students in lectures. Attitudes of students in participating in the lectures will be related to their motivation for completing the process of study on campus. This research will analyze the relationship between learning motivation and attitudes of students in a lecture followed by stress as a variable kontrol. Stress becoming a control variable because stress is a factor that determines the behavior of individuals, thus controlling the level of sress will affect individual behavior. This research using Partial Correlation Analysis to identified correlation between two variables where the other variables considered influential controlled or made permanent (as control variables). In this study by considering the existing limitations, by using judgmental sampling this research took a sample of 73 students. From the results of partial correlation analysis found a correlation between students' learning motivation and attitude where stress levels are controlled (made permanent) is 0.539. This indicates that there is a relationship that is or is not too strong between the motivation to learn the attitudes of students in the lecture if the level of permanent stress. While the relationship is positive because the value of a positive correlation, meaning that the higher the motivation to learn the better the attitude of students in lectures. Significantly there is a relationship between motivation to learn with the students' attitude in lectures STIE AMA Salatiga (t-calculated value = 5.361> t-table value = 1.994) despite the relationship that is or is not too strong (r = 0.539). And direction of the relationship is positive because the value of a positive correlation, meaning that the higher the motivation to learn the better the attitude of students in lectures. Stress variables can be one controlling factor to shape attitudes of students in a lecture, if students can manage stress levels so it can encourage motivation to learn that attitude in following the lectures. Because the correlation between motivation to learn the attitudes of students in following the lectures are not too strong (medium), it can be concluded also that there are factors - other factors affecting the formation of a good attitude in following the lectures to students STIE AMA Salatiga. Keywords : Attitude, Student Behavior, Stress